Capitalizing on the uniqueness of international business: Towards a theory of place, space, and organization - Beugelsdijk, Sjoerd (Journal of International Business Studies, 2022)
The field of international business (IB) has been successful in developing a unique body of knowledge on the multinational corporation and on country-level contexts. A recurring debate concerns its claim to uniqueness, and to associated scholarly characteristics that distinguish IB from other fields of research. I discuss what makes IB research unique by looking at what IB theory can explain and predict. To that end, I leverage key theoretical arguments and empirical insights to advance an understanding of IB centered around a firm's ability to create added value in more than one location. I introduce a stylized model of the multi-locational firm embedded in multiple business systems characterized by equifinality. As a result of the qualitative disjunctures that separate one place from another, multi-locational firms are confronted with additional managerial and organizational challenges. These challenges are rooted in the process of "othering". Theorizing on the critical constructs of place, space, and organization, I argue that IB offers the most generalizable approach to understanding firms doing business in more than one location. IB's ultimate uniqueness lies in the potential of advancing a general theory of the firm in space.